Assessing Christian learning: Towards a practices-based approach to faith, vocation, and assessment. (July 2021) - Smith, David I.; Green, Beth; Kurkechian, Mia; Cheng, Albert
This essay proposes that efforts at assessing the contribution of faith-based schools to faith formation be grounded in an account of student vocation framed by Christian practices. We identify gaps in research on assessment of school effectiveness and suggest that a focus on the present vocation of students may fruitfully connect faith and school-based learning practices. On this basis, we describe a framework for viewing assessment through a practices lens by identifying Christian practices that orient learning practices. We also briefly introduce the Practicing Faith Survey, a new tool based on this approach.